PENGARUH MANAJEMEN BAKAT, MANAJEMEN PENGETAHUAN, PENILAIAN KINERJA, KEPRIBADIAN DAN KREATIVITAS TERHADAP PENGEMBANGAN KARIR PEGAWAI KANTOR KEMENTERIAN AGAMA KABUPATEN PADANG PARIAMAN - Helda Marini; Evi Susanti Tasri (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine the effect of Talent Management, Knowledge Management, Performance Assessment, Personality, and Creativity on the Career Development of the Ministry of Religion's Office employees, Padang Pariaman Regency. The population in this study were all employees the Ministry of Religion, Padang Pariaman Regency, with as many as 62 people. By using the Multiple Linear Regression method. The results of this study indicate that talent management has a positive influence on employee career development at the Office of the Ministry of Religion of Padang Pariaman Regency, Knowledge management has a positive influence on the career development of employees of the Ministry of Religion Office of Padang Pariaman Regency, Performance appraisal has a positive influence on employee career development. Office of the Ministry of Religion of Padang Pariaman Regency, Personality has a positive influence on the career development of employees of the Office of the Ministry of Religion of Padang Pariaman Regency, Creativity has a positive influence on the career development of employees of the Office of the Ministry of Religion of Padang Pariaman Regency.